Prognostic Significance of Thyroglobulin Antibodies in Differentiated Thyroid Cancer. (14th April 2020) - Reverter, Jordi L.; Rosas-Allende, Irene; Puig-Jove, Carlos; Zafon, Carles; Megia, Ana; Castells, Ignasi; Pizarro, Eduarda; Puig-Domingo, Manel; Granada, M. Luisa
Abstract : Objective . To investigate whether variations in thyroglobulin autoantibodies (TgAb) are related to the recurrence or persistence of differentiated thyroid carcinoma (DTC) and may therefore be useful as surrogate tumor markers. Design and Methods . We retrospectively studied 98 subjects (83 women, 47 ± 15 years old) from an initial cohort of 1017 patients treated for DTC in five hospitals, with positive TgAb at any time during the follow-up. Patients presented five different patterns of evolution of serum TgAb concentrations: (1) stable positive TgAb, (2) de novo appearance, (3) an increase of more than 50%, (4) TgAb levels from positive to negative, and (5) a decrease of more than 50%. Results . In the group of 11 patients with stable TgAb, four cases presented persistence of the disease with structural incomplete response. In the group of 22 patients with sustained increasing trend rising more than 50% or de novo detectable TgAb levels, three patients were diagnosed with structural incomplete response. There was no evidence of recurrence or persistence of the disease in any of the 65 patients who showed a significant decrease in ( n  = 35) or disappearance of ( n  = 30) TgAb. Conclusions . Our results suggest that not only the appearance of a significant increase in TgAb but also stable concentrations of TgAb should be regarded as a sufficient risk condition for an active search for recurrent or persistent disease. Conversely, a significant decrease in TgAb levels can represent a good prognostic sign.